Use of the solvent chemistry for the control of the critical thickness of PbTiO3 ultrathin films - Fernandez, R.; Holgado, S.; Huang, Zhaorong; Calzada, M. L.; Ricote, J. (Mrs Materials Research Society, 2010)
The preparation of high-quality ferroelectric PbTiO3-based ultrathin films by chemical solution deposition. using a diol-based sol-gel method, has proved to be successful. However, there is a critical thickness below which the films break up into isolated structures According to previous studies, above a certain grain size to thickness ratio a microstructural instability occurs and the coatings are no longer continuous. We explore the use of the solvent chemistry to control this phenomenon, as an alternative to the more conventional variation of the crystallization parameters. The use of diols with short C chain lengths leads to films with smaller gram sizes, whose critical thicknesses are lower. A reduction from 40 to 15 nm is achieved by reducing the number of C of the chol used from 5 to 2. A critical value of G/t < 5.0 is necessary to obtain continuous ultrathin films with the processing conditions used
Keywords: chemical solution deposition lead titanate films thin-films ferroelectric-films perovskite films fabrication capacitors nanoscale